(untitled) (The Motley Undergraduate Journal, 2024)
This piece works as a critique of neoliberal feminist ideology through an analysis of Anna Melyikan’s 2007 film Mermaid. It begins with a close reading of several scenes in the film and how they operate as a criticism or representation of neoliberal post-Soviet existence. Alissa, the protagonist, is subjected to a series of events which shape her life as a post-Soviet woman—these events ultimately lead to her untimely death. The theme of labour, financially, domestically, and sexually, defines Alissa’s life in Moscow. I use a sociological study on Russian post-Soviet self-help literature written for women as the ideological lens to study the film, drawing connections between the events of the film and the real contents of several self-help books, which are analysed and critiqued by the article’s author. The film visualises a patriarchal double-bind where post-Soviet women are expected to be both patriarchally subordinate and independent economic subjects. This paradox is present in the self-help literature. The essay forges a connection between real-life feminist critique and film criticism, exploring how film criticism can be a vehicle for feminist thought. The essay also interrogates ideas of what a feminist text is and how the creation of a feminist text is an act of discursive meaning-making, a relationship to the viewer/reader as opposed to a definitive quality which takes shape during the text’s creation.